Decarbonization of transport energy installations in the context of sustainable development strategies - Marchenko, Andriy Petrovych; Koruba, Zbigniew (Springer Cham, 2025)
This book explores global challenges related to sustainable development and the environmental impact of human activity, focusing on strategies outlined in the UN Sustainable Development Goals, Industry 4.0, and Industry 5.0. It highlights the role of research and innovation in decarbonizing the economy and ensuring access to clean energy through solutions such as green hydrogen, circular economy principles, and responsible consumption and production. With a particular emphasis on transport energy systems, the book examines decarbonization strategies, hybrid energy systems, thermal pollution, and greenhouse gas emissions, alongside innovations in system design, alternative fuels, process modeling, and the application of digital twins for research and optimization.
Keywords: decarbonization; transport energy installations; sustainable development; Industry 4.0; Industry 5.0; clean energy